Non-Thermal Effect Of The Brand And Generic Mobile Phones Radiofrequency Radiation On The Antioxidant And Histomorphology Of The Epididymis After Prolonged Whole-Body Radiation on Sprague Dawley Rat - Oyedele Oyewumi Ajayi; Johnson Orie Okoro; Daniel Ugbomoiko; Obhioze Augustine Akpoka; Theophilus Ogie Erameh; Efosa Bolaji Odigie (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Mobile phone usage has increased greatly over time, and there is also the proliferation of models by different manufacturers, some of which are known to produce popular brands while other manufacturers of unknown brands have been identified. So many health conditions have been associated with the radiation emitted from mobile phones and other communication gadgets. Such condition as glioma, schwannoma, and some degenerative tissue conditions has been reported by different researchers both on short and prolonged exposure. The IARC report on radiofrequency radiation as a human “possible carcinogen, group 2B” has also prompted much research on the effect of mobile phone radiofrequency radiation on humans. The mobile phone placement in the pocket, which is close to the male reproductive organ, and the possible radiation emission levels from different models by manufacturers prompted this study. The goal is to investigate the histological alterations, spermatic epididymal contents, and changes in oxidative stress indicators that may occur following prolonged exposure to mobile phone radiofrequency radiation. Forty (40) male Sprague Dawley rats were used for this study. They were grouped into eight groups equally, two (2) control groups and six (6) groups that were exposed to six different mobile phone models. The 8 hours of daily exposure for 6 months was done with phones in active mode. The finding showed a significant reduction of the mature sperms in the lumen of the epididymis. There was focal epithelial hyperplasia in two groups exposed to branded models. No degenerative epithelium was observed in the epididymis. There was also a significant reduction in the motility and sperm count of the exposed groups. The Superoxide dismutase (SOD) was significantly depleted across the exposed groups. There are isolated changes that result from individual phone models, but changes cannot be dichotomized into changes that result from branded or generic phones.